Red sky at night - MacKay, Elly (Tundra Books, 2018)
Red sky at night, sailor's delight. And, the next morning, when the dew is on the grass, no rain will come to pass. These are the perfect conditions for a grandfather to take his grandchildren out on a fishing trip. Especially since, as the saying goes, when the wind is from the West, then the fishes bite the best. The family takes a boat out on the lake, fishing and swimming and eventually camping out on a nearby island, taking full advantage of the gorgeous weather. But the next day . . . red sky in the morning, sailors take warning! The family ventures back home just in time to avoid a rainstorm. But not to worry -- the more rain, the more rest. Fair weather's not always best.